Social credibility online: The role of online comments in assessing news article credibility. (March 2018) - Pjesivac, Ivanka; Geidner, Nicholas; Cameron, Jaclyn
This 2 × 2 experimental study (N = 196) tested the effects of source expertise and opinion valence in readers' comments on the credibility of an online news story about genetically modified organisms (GMOs). Source expertise had a significant influence on perceptions of article credibility; articles were judged more credible when public comments embedded in the story were from expert sources (e.g., scientists) rather than nonexpert sources (e.g., Twitter users). Effects were larger on high-frequency news users, regardless of whether comments were for or against GMOs. Results suggest that Internet users mainly use the peripheral or heuristic route of information processing to evaluate online news credibility. The importance for online journalism of social heuristics via opinions of other people is discussed.